2022
DOI: 10.1101/2022.01.24.22269730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic accuracy of chest X-ray interpretation for tuberculosis by three artificial intelligence-based software in a screening use-case: an individual patient meta-analysis of global data

Abstract: Background Chest X-ray (CXR) screening is a useful diagnostic tool to test individuals at high risk of tuberculosis (TB), yet image interpretation requires trained human readers who are in short supply in many high TB burden countries. Therefore, CXR interpretation by computer-aided detection software (CAD) may overcome some of these challenges, but evidence on its accuracy is still limited. We established a CXR library with images and metadata from individuals and risk groups  that underwent TB screening in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…Based on the findings of this study, combined with those of the parallel study conducted by FIND [22], CAD systems may be considered viable as a tool for automated CXR interpretation with regard to TB detection in screening programs, particularly in remote, and/or a high TB burden places where there are limited resources and access to expert radiologists. The use of CAD systems in these areas may even have a wider application and contribute to increase the global TB detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of this study, combined with those of the parallel study conducted by FIND [22], CAD systems may be considered viable as a tool for automated CXR interpretation with regard to TB detection in screening programs, particularly in remote, and/or a high TB burden places where there are limited resources and access to expert radiologists. The use of CAD systems in these areas may even have a wider application and contribute to increase the global TB detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…We selected four commercially available CE-certified TB-specific CAD software: CAD4TB (Delft Imaging, Netherlands), Lunit INSIGHT CXR (Lunit, South Korea), qXR (Qure.ai, India), and InferRead DR Chest (Infervision, China). Three of these software programs (CAD4TB, qXR, Lunit INSIGHT CXR) were part of WHO's recent evidence review, for which performance evaluations were done by FIND, the International Organization of Migration, Stop TB partnership and McGill University and informed the WHO screening guideline [16,[22][23][24];therefore they were included in this study. In September 2021, two software programs (CAD4TB and InferRead) were included in the Stop TB Partnership's Global Drug Facility (GDF) catalogue, which is why InferRead was added to this study.…”
Section: Computer-aided Detection Softwarementioning
confidence: 99%
“…This study was not able to assess the cost effectiveness of the software. According to the literature [23,31], these software programs differ in diagnostic accuracy, which would likely affect the cost effectiveness-something a costing study would not be able to capture. A research study found that the software used to inform the WHO recommendation (qXR, CAD4TB and Lunit) performed significantly better than InferRead, [31].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that triaging thresholds are not universal and require careful adjustment to demographic characteristics, laboratory capacities, budget, healthcare settings and study goals. 2,3,12,13,[4][5][6][7][8][9][10][11] Multiple studies compared the performance among different CAD-software platforms, 11,14,15 but comparisons between software versions are lacking in the literature and are needed to support screening programs when using CAD-software and negotiating software updates.…”
mentioning
confidence: 99%